THE LANDSCAPE OF ITALIAN THEATRE-NATURE: ARTISTS, COMPANIES AND FESTIVALS - Regi , Emanuele; Velardi , Francesca (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This article aims to give a wide range of descriptions about a theatrical phenomenon that in Italy has been spreading since the 2000s: «theatre-nature». With this expression are considered all the performative activities that take place in natural spaces and are created and conceived about them. These forms emerged between the 80s and 90s, but it is from the first years of the 21st century that their diffusion reached many different parts of Italy from the North to the South. Itinerary and site-specific performances, and outdoor theatrical narration are only some of the possible forms that could inhabit the landscape. Companies and single artists might have different theatrical backgrounds (traditional, contemporary or even strictly performative), but they share a common modus operandi in which the ecological relationship with the landscape is crucial to creating the performative fact. We are going to investigate artists and companies (O Thiasos TeatroNatura, Campsirago, Azul Teatro, Teatro Selvatico), but also to analyse their production activities, particularly focusing on a parallel and linked phenomenon: outdoor nature festivals. The traditional theatre building and the structure of cultural funding in Italy are not always aware of «theatre-nature». Therefore, the final issue of this essay is to understand, through festivals, how this phenomenon is created, produced, and distributed.